(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The research aims to determine the impact of banking collateral provided by the client (personal collateral, cash collateral, tangible collateral, and real estate collateral) on the credit-granting decision within a sample of private commercial banks listed on the Damascus Securities Exchange. The descriptive-analytical approach was utilized, and a questionnaire was deployed as the primary study tool. A total of 145 questionnaires were distributed, serving as a comprehensive survey for administrators and employees within the credit departments of the designated private commercial banks listed on the Damascus Securities Exchange. Of these, 125 valid questionnaires were retrieved and subsequently subjected to statistical analysis using the SPSS 25 software. The study yielded several key findings, most notably that a statistically significant impact exists for the banking collateral provided by the client on the credit-granting decision within the investigated banks. Furthermore, a set of recommendations was proposed, emphasizing the activation of regulatory frameworks embodied in the banks’ credit policies. Additionally, emphasis was placed on continuing reforms aimed at enhancing the soundness and stability of the banking sector, thereby substantially contributing to the mitigation of non-performing loans (NPLs). Finally, the necessity of conducting periodic loan reviews was highlighted as a precautionary measure to avert increased default risks and to facilitate the early detection and management of non-performing loans.